2018
DOI: 10.1002/celc.201800729
|View full text |Cite
|
Sign up to set email alerts
|

Mean Intrinsic Activity of Single Mn Sites at LaMnO3 Nanoparticles Towards the Oxygen Reduction Reaction

Abstract: LaMnO 3 has been identified as one of the most active systems towards the 4-electron oxygen reduction reaction (ORR) under alkaline conditions, although the rationale for its high activity in comparison to other perovskites remains to be fully understood. LaMnO 3 oxide nanoparticles are synthesised by an ionic-liquid based method over a temperature range of 600 to 950 8C. This work describes a systematic study of the LaMnO 3 properties, from bulk to the outermost surface layers, as a function of the synthesis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
27
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 31 publications
(85 reference statements)
1
27
0
Order By: Relevance
“…CasaXPS software was used to determine the Pr : Fe ratio for these PFO films which was 1 : (0.7–0.8), showing between 20 and 30 % A‐site surface enrichment at all temperatures (Table S1). A‐site surface segregation is commonly observed in perovskite oxide materials obtained by calcination of molecular precursors, showing a very complex dependence of the nature of the A and B sites and temperature . The Pr surface excess can play a role in charge extraction, although this issue is not assessed in this work.…”
Section: Resultsmentioning
confidence: 97%
“…CasaXPS software was used to determine the Pr : Fe ratio for these PFO films which was 1 : (0.7–0.8), showing between 20 and 30 % A‐site surface enrichment at all temperatures (Table S1). A‐site surface segregation is commonly observed in perovskite oxide materials obtained by calcination of molecular precursors, showing a very complex dependence of the nature of the A and B sites and temperature . The Pr surface excess can play a role in charge extraction, although this issue is not assessed in this work.…”
Section: Resultsmentioning
confidence: 97%
“…[36,37] The main feature of the O 1s spectrum ( Figure 2c) is centered at 530.01 eV, which is assigned to lattice bound oxygen, [13] while the other contributions are linked to surface hydroxyl and carbonylated groups. [38] Fe 2p core-level ( Figure 2d) is significantly more complex to rationalize due to contribution from various phenomena such as multiple-splitting, multiple oxidation states, and charge transfer effects. As a first approximation, the most intense component in 2p 3/2 is at 710.8 eV, with a 13.5 eV splitting from the 2p 1/2 component, which is consistent with a Fe+3 oxidation state.…”
Section: Resultsmentioning
confidence: 99%
“…This behavior is rather unusual for transition metal oxides with the general ABO 3 formula (such as perovskites), which often exhibit different A:B ratio in the bulk and at the surface. [38,40] The optical properties of GFO thin films in the visible range are summarized in Figure 3. The absorption coefficient (α), extracted from transmittance and reflectance spectra of 350 nm films ( Figure S2, Supporting Information) are displayed as a function of the photon energy, revealing several optical transitions between 1 and 3 eV ( Figure 3a).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…14 However, numerous experimental observations have shown that these are only parts of a complex picture, in which surface structure and composition as well as orbital occupancy under electrochemical control also play hugely important roles. [15][16][17][18][19][20] Indeed, electrode potential can introduce substantial changes in surface oxide properties including metal coordination, composition and conductivity. In previous studies, we have linked changes in the oxidation state at the B-site at potentials close to the formal oxygen potential as a key descriptor towards the oxygen reduction reaction to OHunder alkaline conditions.…”
Section: Introductionmentioning
confidence: 99%